2007
DOI: 10.2215/cjn.02380607
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Increased Mortality Risk with Erythropoietin Treatment to Higher Hemoglobin Targets

Abstract: Recent randomized, controlled trials indicate that there is a strong trend for increased risk for death or adverse composite outcomes with erythropoiesis-stimulating agent treatment in kidney disease to hemoglobin targets higher than those currently recommended. The failure of these trials to find a benefit of higher hemoglobin is in stark contrast to findings from large, observational, population-based studies that continue to demonstrate the association of low hemoglobin with adverse outcomes. The mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 60 publications
3
101
1
1
Order By: Relevance
“…We lack the clinical or biomarker-derived tools to characterize precisely risk or potential benefit and thus to individualize our Hb strategy (and this would apply of course to many other treatments, too [e.g., plasma phosphate]). What the precise mechanism(s) might be to explain rHuEPO "toxicity" remains unknown (38); Figure 3 shows some of the many possibilities. A much greater effort is now necessary to understand how, and in whom, benefit can be conferred using these important and powerful medications.…”
Section: Conclusion: Back To the Future?mentioning
confidence: 99%
“…We lack the clinical or biomarker-derived tools to characterize precisely risk or potential benefit and thus to individualize our Hb strategy (and this would apply of course to many other treatments, too [e.g., plasma phosphate]). What the precise mechanism(s) might be to explain rHuEPO "toxicity" remains unknown (38); Figure 3 shows some of the many possibilities. A much greater effort is now necessary to understand how, and in whom, benefit can be conferred using these important and powerful medications.…”
Section: Conclusion: Back To the Future?mentioning
confidence: 99%
“…Recently, studies targeting higher Hb levels or using higher EPO dosing regimens in the correction of anemia have shown detrimental effects including increased all cause mortality, cardiac and cerebral vascular events and vascular access thrombosis 8-10, 54 It is not clear whether this is due to higher HCT or EPO the molecule itself at higher concentration. This review article focused on adjuvant oral and parenteral agents that have been used along with EPO to reduce its dose and give foundation to research in randomized control trials.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that influence the increase in mortality with higher hemoglobin targets may include the impossibility of achieving the target hemoglobin, a too high hemoglobin target, the toxic effects of high doses of ESAs, the presence of comorbidity and other features [131][132][133][134][135] . These factors were evaluated in a second analysis of the CHOIR study [136] that found no clinical factor associated with risk, after adjustment and multivariate analysis, except for high dose of epoetin (> 20 000 U/wk), which was an independent risk factor for death, myocardial infarction, heart failure, or stroke.…”
Section: Hemoglobin Targetmentioning
confidence: 99%